Creating Sustainable Value Within the Second Hand Clothing Supply Chain - Drew, Charles (2016)
The glamorous nature of the fashion industry attracts considerable attention that extends throughout its operation, yet very little is known about what happens to our clothes after we dispose of them. What is known is that 350,000 tonnes of used clothing goes to landfill each year and the same amount is exported to developing countries. This research investigates the workings of the second hand clothing supply chain to understand why these outcomes occur. Utilising sustainable supply chain management and sustainable business models literature this study analyses the performance of the second hand supply chain, and subsequently its ability to create sustainable value. The research finds that the supply chain is fragmented, chaotic and in need of a governing organisation to motivate environmental and social change. Without this motivation the organisations involved at present may find their operations obsolete in the face of contemporary challenges.